Wem gehört die Interkulturalität? Über das Verhältnis von linguistischen Teildisziplinen und Kulturforschung - Csaba Földes (Linguistische Treffen in Wrocław)
Based on the understanding that language is a complex phenomenon that comprises cognitive, cultural, and formal components, this paper systematically focuses on the network of relationships between culture, language, and the communicative act with special consideration of the multidimensional, dynamic, and subtle phenomenon of interculturality as well as its linguistic assessment. This study first discusses in what ways the connection between language and culture is being considered in various areas of scientific discourse. Subsequently, the paper focuses on culturally oriented linguistic approaches, specifically three current and differing research directions that are investigated critically regarding their content profiles, namely (a) the Russian/post-Soviet linguoculturology (LC), (b) the Anglo-American cultural linguistics (CL), and (c) intercultural linguistics (IL) – situated primarily within the field of German Studies – which focuses on interculturality and multilingualism. It can be shown that the targeted field of research is shaped by rather different premises, theories, and methods. The three subfields share the general goal of describing language as a cultural phenomenon as well as culture as a linguistic phenomenon. However, CL predominantly focuses on the influence of culture on language, LC largely investigates the impact of language on culture, and IL addresses inter- and transculturality as its major focal point. Additionally, the underlying cultural concepts seem to diverge significantly: while CL and particularly IL firmly work with a dynamic, semiotic-constructivist understanding of language and culture, the LK publications are mostly based on a static, essentialist-normative viewpoint. Furthermore, the disciplinary positioning and the disposition of the content differ as well: CL and LC exhibit a distinctly cognitive orientation, while IL is based on a contrastive-linguistic and cultural science foundation. Overall, none of the exemplified approaches have yet established a complete theoretical matrix or broad theoretical coherence. CL and LC are most similar in that the problem of conceptualization – though partially based on differing models – takes up much space.